Financial Dependence of Young Adults with Childhood ADHD - Altszuler, Amy R. (J Abnorm Child Psychol, 2016)
This study used data from the Pittsburgh ADHD Longitudinal Study (PALS) to evaluate financial outcomes of young adults (YA) with ADHD relative to comparisons. Participants for this study included 309 individuals who had been diagnosed with ADHD (DSM-III-R or DSM-IV) in childhood and 208 comparison YA without childhood ADHD diagnoses (total N=517) who were followed through age 25. Participants were predominately male (88 %) and Caucasian (84 %). Diagnostic interviews were conducted in childhood. Young adults and their parents reported on financial outcomes and a number of predictor variables. Young adults with ADHD experienced greater financial dependence on family members (p<0.05) and the welfare system (p<0.01) and had lower earnings (p<0.05) than comparisons. ADHD diagnostic status, education attainment, and delinquency were significant predictors of financial outcomes. A projection of lifetime earnings indicated that ADHD group participants could expect to earn $543,000–$616,000 less over their lifetimes than comparisons. Due to the propensity of individuals with ADHD to underreport problems, the data are likely to be underestimates. These findings support the need for interventions to improve labor market outcomes as well as the development of interventions that target the management of personal finances for individuals with ADHD in young adulthood.